Pemahaman Strategi Pencegahan Fraud Dana Desa Bagi Siswa Siswi SMK Ma’arif NU Larangan Brebes - Yusri; Rahmadiane, Ghea Dwi; Nurul (LPPM Universitas Harapan Bangsa Purwokerto, 2024)
The government obliged to provide financial information to village communities in the form of financial reports which aim to prevent conditions from occurring in the management of village fund allocations, so that socialization needs to be formed in terms of preventing village fund fraud because it was an effort to provide deeper knowledge about Public Sector Accounting which is at school. The objectives of this community service activity include increasing new knowledge and insight regarding village fund fraud prevention strategies for students and adding to the repertoire of knowledge, as well as being a reference for other parties who wish to carry out activities with a similar theme. The method of implementing activities in the community service program that carried out related to the discussion of problems expressed by the method of socialization and discussion. The planning to evaluation process calculated for one semester starting from March to June 2023. This service activity included 19 students of the Accounting Department at SMK Ma'arif NU Larangan Brebes. The material presented was material on Village Fund Fraud Prevention. The community service team explained the prevention of village fund fraud. Based on the results, increased knowledge and understanding of village fund fraud prevention.